A descriptive study of the attitudes and practices of health personnel towards clients with STD/HIV - Chipungu, Anne Mulenga Makanta (Lusaka; University of Zambia , School of Medicine, 1995)
STDs are a problem that is common not only to Zambia but to many other nations too. They mainly affect adolescent young adults in all social and economic strata. The current continued spread of STDs is causing great concern hence the need to prevent the further spread of them. In order to find out why STDs were on the increase, a research into the attitudes of health personnel towards clients with STDs/HIV.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Nursing.
Includes bibliographical references.
Keywords: HIV Infections; Public health personnel --attitudes.